2019
DOI: 10.25165/j.ijabe.20191202.4245
|View full text |Cite
|
Sign up to set email alerts
|

Micro-nondestructive detection of the moisture and ion of rice seeds during germination under salt stress

Abstract: Salt stress is one of the major stress factors limiting rice productivity. Its damaging effects include water deficit due to osmotic stress, and ionic toxicity caused by ionic stress. It is very important to study the salt-tolerance mechanism of rice under salt stress, in order to improve the salt-tolerance capacity of rice and thereby increase the yield. In this experiment, the low field nuclear magnetic resonance (LF NMR) technique and the traditional dry-weight weighing method, the non-invasive micro-test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Low-field nuclear magnetic resonance (LF-NMR) technology can test samples rapidly, accurately, and non-destructively [22][23][24] , and can analyze the internal water phase, distribution characteristics, and flow characteristics of samples at a submicroscopic level [25][26][27] . Thus, it can reveal the internal water state and patterns of change during the germination of crop seeds [28,29] .…”
Section: Introductionmentioning
confidence: 99%
“…Low-field nuclear magnetic resonance (LF-NMR) technology can test samples rapidly, accurately, and non-destructively [22][23][24] , and can analyze the internal water phase, distribution characteristics, and flow characteristics of samples at a submicroscopic level [25][26][27] . Thus, it can reveal the internal water state and patterns of change during the germination of crop seeds [28,29] .…”
Section: Introductionmentioning
confidence: 99%
“…Mahlangu et al [10] found 120 mg/L N in nutrient solution could get the largest fresh weight of lettuce crown. Moreover, Chinese cabbage and lettuce were considered to grow best in nutrient solutions with an N concentration of 112 mg/L [11] . However, excessive N application will cause many negative effects [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of water state change of materials during drying is important for prediction of dehydration. Low field nuclear magnetic resonance (LF-NMR), an excellent noninvasive tool, is an advantageous choice for analyzing dynamic water states of product during drying with high sensitivity and short detection time [17] . The change in relaxation time in LF-NMR was used to explain the water mobility and distribution inside the sample from a microscopic point of view.…”
Section: Introductionmentioning
confidence: 99%